1996
DOI: 10.1016/0378-1097(95)00505-6
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of Mycobacterium leprae: Recent insight

Abstract: Leprosy is still a health problem in many countries. Because the causative organism, Mycobacterium leprae cannot be cultured in vitro, it is virtually impossible to assess exposure, and the onset of infection and disease. As a consequence, the chain of infection, considered as the relationships between M. leprae, transmission and human host, is poorly understood. Here, we discuss a number of organism-, host- and environmental-related factors which may be incriminated in the dynamic process of the development o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 1 publication
1
34
0
5
Order By: Relevance
“…Health professionals in these regions must remain alert to the clinical classifi cation of the index case and the kinship with the exposed HC, as these constitute risk factors for the disease (11) . A previous study reported that HC have a high risk of leprosy (12) . A previous study reported a higher incidence of APGL-I positivity among HC than among the general population (6) .…”
Section: Methodsmentioning
confidence: 96%
“…Health professionals in these regions must remain alert to the clinical classifi cation of the index case and the kinship with the exposed HC, as these constitute risk factors for the disease (11) . A previous study reported that HC have a high risk of leprosy (12) . A previous study reported a higher incidence of APGL-I positivity among HC than among the general population (6) .…”
Section: Methodsmentioning
confidence: 96%
“…A região é dividida em quatro distritos, sendo o segundo a área deste estudo. 3 Evidências mostram que pessoas que co-habitam com pacientes hansenianos têm risco aumentado de desenvolver a doença 4,5 e contatos domiciliares de pacientes multibacilares têm risco entre cinco e 10 vezes maior de desenvolver a doença do que a população geral, [5][6][7] além de que o tipo de contato não se limita aos intrafamiliares, mas se estendem às relações de vizinhança e sociais. 5,6 O risco estimado é aproximadamente quatro vezes maior entre os vizinhos diretos do que em indivíduos que não tiveram contato com os pacientes.…”
Section: Introductionunclassified
“…It is well known that contacts of leprosy patients have an increased risk of developing leprosy compared to the general population (13). Several studies have shown that the majority of new patients have a contact relation with another patient (8,14).…”
mentioning
confidence: 99%